2023
DOI: 10.1155/2023/2806835
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Phylogenetic Analysis of Hepatitis E Virus (HEV) Strains from Pigs Farmed in Eight European Countries between 2020 and 2022

Luca De Sabato,
Giovanni Ianiro,
Giovanni L. Alborali
et al.

Abstract: In high-income countries, the hepatitis E virus (HEV) is considered an emerging threat causing autochthonous acute hepatitis in humans, with an increased number of reported cases over the last 10 years and related increased burden of chronic hepatitis in immunocompromised and transplant patients. Pigs are the main reservoir of the HEV-3 genotype, which is the most common in Europe, and can be transmitted to humans through the consumption of raw and undercooked pork products. Extensive sequencing revealed the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…The Canadian pork isolates mostly belong to subtypes 3a and 3b [ 22 , 23 ]; therefore, the presence of a few clinical isolates in Canada that belong to subtypes 3c, 3e, 3f, and 3g could be attributed to the consumption of imported meat products, or possibly travel to endemic regions of Europe. An extensive phylogenetic analysis of HEV-3 isolated from farmed pigs in Europe has also revealed that subtypes 3c, 3e, 3f, and 3g are most common, while there are only a few isolates that belong to 3a, and 3b [ 35 ]. Furthermore, it has been indicated that subtypes e, f, g are associated with a more severe disease presentation [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Canadian pork isolates mostly belong to subtypes 3a and 3b [ 22 , 23 ]; therefore, the presence of a few clinical isolates in Canada that belong to subtypes 3c, 3e, 3f, and 3g could be attributed to the consumption of imported meat products, or possibly travel to endemic regions of Europe. An extensive phylogenetic analysis of HEV-3 isolated from farmed pigs in Europe has also revealed that subtypes 3c, 3e, 3f, and 3g are most common, while there are only a few isolates that belong to 3a, and 3b [ 35 ]. Furthermore, it has been indicated that subtypes e, f, g are associated with a more severe disease presentation [ 29 ].…”
Section: Resultsmentioning
confidence: 99%